ANALISIS KOMODITI UNGGULAN DAN PERTUMBUHAN SUBSEKTOR TANAMAN PANGAN DI PROVINSI SUMATERA SELATAN - Sily Aristi; Putri ayu ogari (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2022)
This study aims to analyze the main food crop commodities in South Sumatra Province and analyze the growth of food crop commodities in South Sumatra Province during 2011-2015. The location determination was carried out purposively because it was based on the consideration that South Sumatra Province is one of the provinces in terms of agriculture, especially the food crops subsector, which has considerable potential for natural resources and human resources in improving the regional economy. The method used in this research is a literature study method where the author uses secondary data (Time Series) or a time series from 2011 to 2015. The results showed using the Location Qoutient (LQ) analysis tool that the pre-eminent food crop sub-sector in South Sumatra Province from 2011 to 2015 was rice food crops, while non-superior food crops consisted of corn, cassava, sweet potatoes, peanuts, green beans and soybeans. Meanwhile, growth (Shift share) shows that the growth of food crop commodities in South Sumatra Province from 2011 to 2015 crops of rice, corn, cassava, and soybeans had good growth by showing positive numbers, while the commodity of sweet potatoes, peanuts, Soil, and green beans have poor growth in South Sumatra Province where the shift share results show a negative value.Keywords: Leading Commodity, Growth, LQ Analysis and Shift Share